This test uses JavaScript to generate your test and mark it. You therefore need to enable Scripting using the Preferences... item in one of the Menu items for this Browser's window. Once enabled, just Reload (Refresh) this page.

Polynomials: Differentiation Rules

Using the Chain Rule, differentiate q = ( x – 2 )3
dq
---
dx
= ( x + ) ( x + )

tickcross


Worked Solution:

The Chain Rule
y = u(v(x))=>
dy
---
dx
=
du
---
dv
×
dv
---
dx
Here y is q, u = v3 and v = x – 2
=>
du
---
dv
= 3v 2  and 
dv
---
dx
= 1
=>
dq
---
dx
= 3 (x – 2)2(1)
dq
---
dx
= 3 (x – 2)2


© MEI Produced by Dr Ron Knott, revised 15 May 2007
tom . button [AT] mei . org . uk
Test reference: PolyDiffRules.html?ref=81157,qu=chain